The Application of Flexibility Concept on East Java’s Art Auditorium - Galuh Fajarwati; Asri Dinapradipta; Vincentius Totok Noerwasito (Institut Teknologi Sepuluh Nopember, 2020)
East Java art has a diversity of types and forms of performances. There are types of performances in the form of theatrical and ballet performances. This traditional art performance is intended to convey messages, advice, and past stories. This presentation is presented with various types of art so that between the types of theatrical or dance performances, each has a variety of needs for its stage and capacity. However, the lack of staging facilities is one of the problems that result in reduced artistic activities, so that some traditional arts in East Java are threatened with extinction. In this study, the purpose of this study is to look for patterns of flexibility in the auditorium to meet the needs of East Java art activities. The method used is the observation method. The observation was carried out by observing each type of East Java art activities to be accommodated, namely the type of traditional dance and theater. The selected arts are several art representatives who have the same type of performance. From the results of data analysis it can be concluded that the auditorium can at least adapt to 4 types of spatial configurations: arena, endstage, proscenium, and plaind stage.